A guide to private prescribing. Issue 6 (19th March 2015) - Steele, Sarah; Freitag, Andreas; McGettigan, Patricia; Giovannoni, Gavin; Pollock, Allyson M
Abstract : Under what circumstances can healthcare professionals issue a private prescription? This article explores the various options.